Impact of fermented organic fertilizers on in-situ trace gas fluxes and on soil bacterial denitrifying communities in organic agriculture - Schauß, Kristina; Justus Liebig University Giessen (My University, 2006)
In the present study, in-situ N2O and CH4 fluxes were quantified in organic agriculture. Trace gas fluxes were observed in winter wheat and spring wheat within an organic cropping system without livestock as well as in spelt and potatoes within an organic cropping system with livestock. Thereby, the impact of different manuring treatments based on the fermentation of cattle slurry and/or plant biomass in biogas reactors was investigated in comparison to the respective, common manuring practices. In the cropping system without livestock, green manures, intercrops, and crop residues were anaerobically fermented and used for manuring in contrast to the common mulching practice. In the cropping system with livestock, cattle slurry or cattle slurry and intercrops and crop residues were fermented and then applied as fertilizer in comparison to the common slurry and farmyard manure practice. The same crops and manuring treatments were investigated during three years (2002/2003 - 2004/2005). After 3.5 years of different manuring regimes, field soil samples were compared with respect to the microbial nitrogen and carbon metabolism. In the laboratory, incubation experiments were carried out to assess the N2O and CH4 evolution from the fertilizers themselves, i.e. from raw slurry, fermented slurry, and fermented crop material under optimum conditions for denitrification. Furthermore, a three-week fertilization experiment was conducted in the greenhouse with spring wheat to investigate in more detail the impact of the different organic manures (raw slurry, fermented slurry, and fermented crop material) on the N2O emissions and the soil denitrifiers.

Im Rahmen der vorliegenden Arbeit wurden N2O- und CH4-Flüsse in einem Winter- und Sommerweizenbestand eines viehlosen ökologischen Betriebssystems und in einem Dinkel- und Kartoffelbestand eines viehhaltenden ökologischen Betriebssystems in-situ quantifiziert. Dabei wurden die Einflüsse von Düngevarianten basierend auf der Vergärung von Rindergülle und/oder pflanzlicher Biomasse in Biogasanlagen auf die Spurengasflüsse vergleichend zu den sonst gängigen Düngestrategien untersucht. Im viehlosen Betriebssystem wurden im Vergleich zur üblichen Mulchwirtschaft die Schnitte der Gründüngungsrotation, die Zwischenfruchtaufwüchse sowie die Erntereste fermentiert und zur Düngung genutzt. Im viehhaltenden Betriebssystem wurde Rindergülle bzw. Rindergülle, Zwischenfruchtaufwüchse, Ernte- und Futterreste in Biogasanlagen vergoren und als Dünger appliziert und mit der üblichen Gülle- und Stallmistwirtschaft verglichen. Die gleichen Bestände und Düngesysteme wurden während drei Jahren (2002/2003 - 2004/2005) beprobt, um die Witterungseinflüsse besser einschätzen zu können. Nach 3,5 Jahren differenzierten Düngemanagements wurden verschiedene biologische und chemische Parameter, die in Beziehung zum mikrobiellen Stickstoff- und Kohlenstoffmetabolismus stehen, in den Feldbodenproben aus allen Düngesystemen analysiert. Des weiteren wurde in einem Inkubationsexperiment unter optimalen Denitrifikationsbedingungen die N2O-und CH4-Entwicklung aus den reinen Düngern Rohgülle, vergorene Gülle und vergorenes Pflanzenmaterial gemessen. Im Gewächshaus wurde ein dreiwöchiges Düngungsexperiment mit Sommerweizen durchgeführt, um die Wirkungen von Rohgülle, vergorener Gülle und vergorenem Pflanzenmaterial auf die bodenbürtigen N2O-Emissionen sowie auf die denitrifizierenden Bakterien detaillierter zu untersuchen.
Einfluss fermentierter organischer Dünger auf Spurengasemissionen und bodenbakterielle Denitrifizierergemeinschaften im Ökologischen Landbau
Keywords: N2O; CH4; Denitrifizierer; Ökologischer Landbau; real-time PCR; nitrous oxide; methane; denitrifying bacteria; organic agriculture; real-time PCR; ddc:630